High blood pressure in menopausal women – therapeutic implications - Posadzy-Małaczyńska, Anna (Przewodnik Lekarza/Guide for GPs, 2006)
High blood pressure is among the main determinants of cardiovascular disease risk in women. Epidemiological data on women around menopause are scant and in particular there is the relationship between menopausal status and hypertension. More than 30 years ago women participating, were smaller part of a large study of hypertension. Thus, they cannot be considered representative of population to show indications to management of hypertension. Epidemiological evidence on the role of menopause and hypertension and the choice of drug and hormone replacement therapy (HRT) regimen are inconsistent and their status is steel an open question. Long term follow-up studies are needed to gain a better understanding of the treatment of hypertension and effective therapy with hormone replacement.